Type I flavohemoglobin of mycobacterium smegmatis is a functional nitric oxide dioxygenase. Issue 6 (26th May 2014) - Thakur, Naveen; Gupta, Sanjay; Hade, Mangesh Dattu; Dikshit, Kanak L.
Abstract Two flavohemoglobins, type I and type II, displaying distinct structural features and cofactor binding sites coexist in Mycobacterium smegmatis; however, none of these flavohemeproteins are characterized so far. We have cloned and expressed type I flavohemoglobin (FHb1) of Mycobacterium smegmatis, encoded by MSMEG_1336, and characterized its spectral and functional properties. FHb1 exists as a monomer and displays spectral and functional characteristics similar to HMP of E. coli. Specific NO dioxygenase (NOD) activity of FHb1 was estimated to be 63.5 nmol heme−1 sec−1, which was nearly eightfold higher than the HbN of M. tuberculosis and matched closely to the HMP of E. coli on the basis of cellular heme content. FHb1 preferred NADH for the NO dioxygenation and exhibited rapid reduction of flavin adenine dinucleotide and heme iron using NADH as electron donor. Level of FHb1 transcript increased significantly in M. smegmatis in the presence of acidified nitrite, and a nitric oxide‐responsive transcriptional regulator of Rrf2 family exists together with the FHb1 under the same operon. These results suggested that FHb1 of M. smegmatis is a functional NOD and may be involved in the stress management of its host toward nitric oxide and nitrosative stress. © 2014 IUBMB Life, 66(6):396–404, 2014